MiRNA miR‐17‐92 cluster is differentially regulated in the imiqumod‐treated skin but is not required for imiqumod‐induced psoriasis‐like dermatitis in mice. Issue 1 (January 2017) - Wu, Dinghong; Bi, Xinling; Qu, Le; Han, Ling; Yin, Congcong; Deng, Jingwen; Dong, Zheng; Mi, Qing‐Sheng; Zhou, Li
Abstract: MicroRNAs (miRNAs) play very important roles in the control of immune cell and keratinocyte development and function and are implicated in skin inflammatory diseases, including psoriasis. miRNA miR‐17‐92 was reported to promote the differentiation of Th1 and Th1 cells and to regulate cell proliferation and apoptosis. Here we showed that imiquimod (IMQ) differentially regulates the expression of miR‐17‐92 cluster in the mouse skin, upregulating miR‐17 and miR‐19 families and downregulating miR‐92. To investigate whether miR‐17‐92 cluster is functionally involved in the psoriasis, we have generated three mutant mice with specific deletion or overexpression of miR‐17‐92 cluster in keratinocytes, or with deletion of miR‐17‐92 cluster in T cells. Interestingly, deletion or overexpression of miR‐17‐92 cluster in keratinocytes, or deletion of miR‐17‐92 in T cells did not significantly affect IMQ‐induced psoriasis‐like dermatitis development in the mutant mice compared with wild‐type littermates. Thus, miRNA miR‐17‐92 cluster may not be a key factor regulating imiqumod‐induced psoriasis‐like dermatitis.